2010
DOI: 10.1212/wnl.0b013e3181eee40f
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and recurrent intracerebral hemorrhage in cerebral amyloid angiopathy

Abstract: Objective: To identify and compare clinical and neuroimaging predictors of primary lobar intracerebral hemorrhage (ICH) recurrence, assessing their relative contributions to recurrent ICH.Methods: Subjects were consecutive survivors of primary ICH drawn from a single-center prospective cohort study. Baseline clinical, imaging, and laboratory data were collected. Survivors were followed prospectively for recurrent ICH and intercurrent aspirin and warfarin use, including duration of exposure. Cox proportional ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
259
3
20

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(293 citation statements)
references
References 29 publications
(39 reference statements)
10
259
3
20
Order By: Relevance
“…3,5 A recent, large meta-analysis of case-control studies conclusively demonstrated that APOE e2 and e4 increase risk of ICH in the lobar brain regions. 6 An intriguing preliminary finding that emerged as well was an association between APOE e4, but not e2, and nonlobar ICH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,5 A recent, large meta-analysis of case-control studies conclusively demonstrated that APOE e2 and e4 increase risk of ICH in the lobar brain regions. 6 An intriguing preliminary finding that emerged as well was an association between APOE e4, but not e2, and nonlobar ICH.…”
Section: Resultsmentioning
confidence: 99%
“…2 Previous studies demonstrated that survivors of ICH in the lobar brain regions are at higher risk of recurrence, and multiple predictors of recurrent lobar ICH have been identified. 3,4 Among these, the e2/e4 variants of the APOE gene are presumed to modify lobar ICH recurrence risk via their role in small vessel disease associated with cerebral amyloid angiopathy (CAA). 3,5 A recent, large meta-analysis of case-control studies conclusively demonstrated that APOE e2 and e4 increase risk of ICH in the lobar brain regions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that these abnormalities might render cortical-subcortical vessels more vulnerable to rupture and with less potential for tamponade compared to deep perforating arteries in the presence of excessive anticoagulation. 17,18 In addition, evidence supporting a link between CAA and OAC-ICH includes the demonstration that the APOE e2 allele, a known genetic risk factor of CAA-related lobar ICH, 19,20 is more common in warfarin-associated ICH than in control patients on warfarin without ICH, 8 and that individual cases of ICH following anticoagulation or coronary thrombolysis revealed advanced CAA on autopsy. 21,22 Our findings are in apparent disagreement with those derived from the PITCH study by DequatrePonchelle et al 12 who found no influence of OACs on the anatomical distribution of ICH but a significant effect of these compounds on the volume of deep brain hematomas.…”
Section: Statistical Analyses Differences Among the Treatment Groupsmentioning
confidence: 99%
“…The microbleed burden could have significant implications for anti-platelet treatment in patients with CAA. 47 A subanalysis of the Perindopril protection against recurrent stroke study (PROGRESS) suggests that blood pressure control reduces the risk of CAA-related ICH and blood pressure lowering could be preventive against multiple causes of ICH. 48 Animal studies in mice suggest that AB immunotherapy could theoretically slow or stop the development of CAA; however, it remains unclear if these findings are applicable in humans.…”
Section: Prospects For Prevention and Treatmentmentioning
confidence: 99%